HUBUNGAN CARA BELAJAR DENGAN HASIL BELAJARMAHASISWA PADA MATA KULIAH PELAYANAN KELUARGA BERENCANA DI STIKESMITRA ADIGUNA PALEMBANG TAHUN 2014 - Septa Orienzah (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2016)
The background of this study was based on the low learning outcomes of students in the course planning services in High School Of Health Sciences Mitra Adiguna Palembang, 200 students only 2.5% mendpat A, 21.25% got a B, 30% got a C, and 46 , 25% received a D. necessitating research on